2022
DOI: 10.1126/sciadv.add0285
|View full text |Cite
|
Sign up to set email alerts
|

Concentrated poverty, ambient air pollution, and child cognitive development

Abstract: Why does growing up in a poor neighborhood impede cognitive development? Although a large volume of evidence indicates that neighborhood poverty negatively affects child outcomes, little is known about the mechanisms that might explain these effects. In this study, we outline and test a theoretical model of neighborhood effects on cognitive development that highlights the mediating role of early life exposure to neurotoxic air pollution. To evaluate this model, we analyze data from a national sample of America… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
3
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 25 publications
(10 citation statements)
references
References 61 publications
0
10
0
Order By: Relevance
“…Historically marginalized communities are disproportionately impacted by environmental pollution and suffer the brunt of severe health outcomes from toxic exposures. Living in high poverty neighborhoods has been associated with increased air pollution exposure in early childhood and reduced cognitive ability by 0.10 standard deviations by age four (Wodtke et al 2013 ). Furthermore, schools with higher proportions of students of color and students on free and reduced lunch programs have disproportionately higher exposure to air pollution and proximity to sources of lead emissions (Oliva and Som 2022 ; Cheeseman et al 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…Historically marginalized communities are disproportionately impacted by environmental pollution and suffer the brunt of severe health outcomes from toxic exposures. Living in high poverty neighborhoods has been associated with increased air pollution exposure in early childhood and reduced cognitive ability by 0.10 standard deviations by age four (Wodtke et al 2013 ). Furthermore, schools with higher proportions of students of color and students on free and reduced lunch programs have disproportionately higher exposure to air pollution and proximity to sources of lead emissions (Oliva and Som 2022 ; Cheeseman et al 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…Such effects could occur for several reasons. For instance, disadvantaged neighborhoods may lack institutional resources that promote academic achievements, such as high-quality schools, daycare centers, and recreational areas (Brooks-Gunn 1997;Small and Newman 2001;Wilson 2012), and offer physical conditions that affect children's educational prospects, such as toxics, air population, noise pollution, and poor housing conditions (Clark et al 2017;Moonie et al 2006;Wodtke et al 2022). Further, the neighborhood context may matter through peer interactions and socialization of children by older peers and adults (Jencks and Mayer 1990;Sampson et al 2002;Sharkey and Faber 2014;Wodtke et al 2011).…”
Section: From Neighborhood Disadvantage To Educational Disparitiesmentioning
confidence: 99%
“…The dimensions of cognitive abilities affected by air pollution are several. For example, studies have found PM2.5 to hinder the development of working memory (Alvarez-Pedrerol et al 2017), to determine differences in brain structure (Cserbik et al 2020), to reduce pattern construction (Milojevic et al 2021), while one study documented air pollution as mediating the impact of neighborhood poverty on child cognitive development (Wodtke et al 2022). Similarly, students attending schools located in the proximity of industrial facilities, power plants and highways have a higher risk of neurological diseases (Kweon et al 2018) and lower test scores (Persico and Venator 2019).…”
Section: Air Pollution and Educational Achievementmentioning
confidence: 99%